'Terrible Panizzi': Patriotism and Realism of the 'Prince of Librarians'. Issue 5 (18th August 2018) - Gambari, Stefano; Guerrini, Mauro
Abstract: This article deals with the figure of Antonio Panizzi, considered as an Italian patriot and English librarian. It highlights the constant attention he devoted to the Italian political events throughout his life: from his arrival in London (1823) as a political exile, to his informal ambassador in United Kingdom, a role that allowed him to lobby the political class and the press on behalf of the cause of Italian patriots forced in the prisons of Kingdom of the Two Sicilies. The article describes the multifaceted library activity carried out by Panizzi at the British Library, of which he became Principal Librarian in 1856. Panizzi is considered to be the first Promethean Librarian of the 19th century, a great reformer with new ideas on library services, innovative methodologies, and working practices in librarianship. Panizzi rigorously carried out the activity of librarian at the British Library without ever forgetting the need for a free, unified, and democratic Italian state.